2008
DOI: 10.1021/la703583u
|View full text |Cite
|
Sign up to set email alerts
|

A Compact Functional Quantum Dot−DNA Conjugate:  Preparation, Hybridization, and Specific Label-Free DNA Detection

Abstract: In this letter, we report the preparation of a compact, functional quantum dot (QD)-DNA conjugate, where the capturing target DNA is directly and covalently coupled to the QD surface. This enables control of the separation distance between the QD donor and dye acceptor to within the range of the Förster radius. Moreover, a tri(ethylene glycol) linker is introduced to the QD surface coating to effectively eliminate the strong, nonspecific adsorption of DNA on the QD surface. As a result, this QD-DNA conjugate h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
116
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(118 citation statements)
references
References 40 publications
2
116
0
Order By: Relevance
“…17 Most of the reported approaches required covalent conjugation of DNA to the QD surface (e.g., by EDC/NHS coupling reaction), which often decreases the colloidal stability and/or the emission intensity of QDs. 18,19 This limitation can be overcome by the use of a sensing platform relying on the electrostatic interaction of dye-labeled DNA with the oppositely charged QD surface 20 in a similar fashion as in conducting polymer-based detection assays. 4Ϫ8 In this paper, we propose a simultaneous use of conjugated polymers and semiconductor QDs for DNA hybridization detection, which can potentially combine advantages of both light-harvesting and DNA-binding properties of water-soluble polymers with photostability, lightharvesting ability, and FRET donor property of QDs.…”
mentioning
confidence: 99%
“…17 Most of the reported approaches required covalent conjugation of DNA to the QD surface (e.g., by EDC/NHS coupling reaction), which often decreases the colloidal stability and/or the emission intensity of QDs. 18,19 This limitation can be overcome by the use of a sensing platform relying on the electrostatic interaction of dye-labeled DNA with the oppositely charged QD surface 20 in a similar fashion as in conducting polymer-based detection assays. 4Ϫ8 In this paper, we propose a simultaneous use of conjugated polymers and semiconductor QDs for DNA hybridization detection, which can potentially combine advantages of both light-harvesting and DNA-binding properties of water-soluble polymers with photostability, lightharvesting ability, and FRET donor property of QDs.…”
mentioning
confidence: 99%
“…Distilled water was used in the experiment. Briefly, the water-soluble CdSe quantum dots were synthesized by using thioglycolic acid as stabilizer in aqueous solution under N 2 because QDs have high affinity for thiols [7]. The quinoline derivatives with amine group reacted with the QDs containing carboxylic acid functional group.…”
Section: Methodsmentioning
confidence: 99%
“…In order to improve the photoluminescence quantum yield and stability, CdTe/CdS and CdTe/CdS/ ZnS core-shell composite QDs have been successfully prepared in an aqueous phase assisted by microwave irradiation [2], which exhibit excellent photostability and favorable biocompatibility. In addition, the broad absorption and narrow emission spectra of the QDs make them excellent donors in fluorescence resonance energy transfer (FRET)-based sensors, because these fluorescence characteristics allow the selection of a wide range of excitation wavelengths to minimize the background due to direct excitation of the acceptor [4,5]. Hering et al reported that fluorescent proteins from the green fluorescent protein (GFP) family interact strongly with CdSe/ZnS quantum * corresponding author; e-mail: xueningfei888@126.com dots.…”
Section: Introductionmentioning
confidence: 99%
“…Several sensor designs based on FRET between QDs and dye-labeled biomolecules have been developed [142][143][144]. Zhou et al reported preparation and specific label-free DNA detection of a compact, functional QD-DNA conjugate [145]. Target DNA (DNA-T) was immobilized on the surface of the functional QD.…”
Section: Quantum Dotsmentioning
confidence: 99%
“…one, which was complementary to the target sequence of interest (5Õ GGATTATTGTT Figure 12. Principles of the approaches for hybridization and label-free detection of DNA probes with a covalently-coupled QD-DNA-T conjugate via a QD-sensitized FRET signal [145]. Figure 13.…”
Section: Trends Inmentioning
confidence: 99%